Effects of transcranial direct current stimulation (t-DCS) of the cerebellum on pain perception and endogenous pain modulation: a randomized, monocentric, double-blind, sham-controlled crossover study - Stacheneder, Regina; Alt, Laura; Straube, Andreas; Ruscheweyh, Ruth (The cerebellum, 2023)
Accumulating evidence demonstrates a role of the cerebellum in nociception. Some studies suggest that this is mediated via endogenous pain modulation. Here, we used t-DCS to test the effects of modulation of cerebellar function on nociception and endogenous pain modulation. Anodal, cathodal, and sham cerebellar t-DCS were investigated in a cross-over design in 21 healthy subjects. The nociceptive flexor (RIII) reflex, conditioning pain modulation (CPM), and offset analgesia (OA) paradigms were used to assess endogenous pain modulation. Somatosensory evoked potentials (SEPs) and pain ratings were used to assess supraspinal nociception and pain perception, respectively. No significant t-DCS effects were detected when including all t-DCS types and time points (baseline, 0, 30, 60 min post t-DCS) in the analysis. Exploratory analysis revealed an increased RIII reflex size immediately after cathodal t-DCS (compared to sham, P = 0.046, η2p = 0.184), in parallel with a trend for a decrease in electrical pain thresholds (P = 0.094, η2p = 0.134), and increased N120 SEP amplitudes 30 min after cathodal compared to anodal t-DCS (P = 0.007, η2p = 0.374). OA was increased after anodal compared to sham stimulation (P = 0.023, η2p = 0.232). Exploratory results suggested that cathodal (inhibitory) cerebellar t-DCS increased pain perception and reduced endogenous pain inhibition while anodal (excitatory) t-DCS increased endogenous pain inhibition. Results are principally compatible with activation of endogenous pain inhibition by cerebellar excitation. However, maybe due to limited t-DCS skull penetration, effects were small and unlikely to be clinically significant.
Online veröffentlicht: 08. Dezember 2022
Gesehen am 04.06.2024